Is liquidity associate to profitabilitry? An analysis of the retail industry in Portugal - Velez, Afonso Miguel De Melo Tomaz Diogo (2020)
This Work Project analyses the relationship betweenliquidity, proxied by Cash Conversion Cycle and Liquidity Ratios,and Return on Assets, namely how and to what extent these variables associate.Based on a sample of Portuguese retail companies forthe period 2016-2018,the results show thatDays Payable Outstanding and Days Sales Outstanding havea significant influence in profitabilitywhereasDays Inventory Outstanding doesnot. Moreover, liquidity profiles and sources of profitability differ between smallerand biggercompanies.The research is relevant to working capital management and addresses to managers whocan improve profitabilityby reducing liquidity.